PRAGMATIC TRANSLATION - Inog’omjonova Robiya Rustamjon qizi (Galaxy International Interdisciplinary Research Journal, 2024)
This article explores the concept of pragmatic translation, which prioritizes effective communication over strict adherence to the original text. The author discusses how pragmatic translation takes into account cultural and linguistic differences between languages, as well as the intended audience for the translation. The article highlights the importance of adjusting the wording, tone, and style of the original text to ensure clarity and appropriateness for the target audience.